2023
DOI: 10.1093/ecco-jcc/jjac190.0123
|View full text |Cite
|
Sign up to set email alerts
|

DOP83 Proactive dosing is superior to clinically based dosing in terms of endoscopic healing in paediatric patients with Crohn’s disease receiving maintenance infliximab: A randomized controlled trial

Abstract: Background Proactive dosing based on drug monitoring of adalimumab has been reported to be associated with higher rates of clinical remission in children with Crohn’s disease (CD). We aimed to investigate whether proactive drug monitoring of infliximab (IFX) is associated with higher rates of endoscopic healing (EH) in paediatric patients with CD. Methods We conducted a nonblinded, randomized controlled trial of 112 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…71 An RCT from South Korea, encompassing 112 biologic-naive children with CD who responded to induction treatment with infliximab, demonstrated the superiority of proactive TDM over clinically based dosing in sustained corticosteroid-free clinical remission and endoscopic healing. 72 A retrospective single-center study assessing outcomes in pediatric patients receiving either infliximab or adalimumab before (pre-TDM; 72.2% received infliximab) and after the implementation of institutional guidelines for proactive TDM (post-TDM; 65.5% received infliximab) found that proactive TDM improved key clinical outcomes, including sustained clinical remission, the incidence of high ATI titer, and anti-TNF cessation related to ATI. 73 The prospective Precise Infliximab Exposure and Pharmacodynamic Control (REMODEL-CD) study is investigating the safety and effectiveness of personalized dosing of infliximab with specific PK and pharmacodynamic (PD) targets from the start of therapy using a “PK dashboard” for children and young adults with CD (NCT05660746; cf.…”
Section: Whom To Monitormentioning
confidence: 99%
“…71 An RCT from South Korea, encompassing 112 biologic-naive children with CD who responded to induction treatment with infliximab, demonstrated the superiority of proactive TDM over clinically based dosing in sustained corticosteroid-free clinical remission and endoscopic healing. 72 A retrospective single-center study assessing outcomes in pediatric patients receiving either infliximab or adalimumab before (pre-TDM; 72.2% received infliximab) and after the implementation of institutional guidelines for proactive TDM (post-TDM; 65.5% received infliximab) found that proactive TDM improved key clinical outcomes, including sustained clinical remission, the incidence of high ATI titer, and anti-TNF cessation related to ATI. 73 The prospective Precise Infliximab Exposure and Pharmacodynamic Control (REMODEL-CD) study is investigating the safety and effectiveness of personalized dosing of infliximab with specific PK and pharmacodynamic (PD) targets from the start of therapy using a “PK dashboard” for children and young adults with CD (NCT05660746; cf.…”
Section: Whom To Monitormentioning
confidence: 99%